Effect of Kinesiology Tape on Muscle Activation of Lower Extremity and Ankle Kinesthesia in Individuals With Unilateral Chronic Ankle Instability - Yin, Lulu; Liu, Kun; Liu, Chengmei; Feng, Xiaodong; Wang, Lin (Frontiers in Physiology, 2021)
Background: The purpose of the study was to determine the effect of kinesiology tape (KT) on lower limb muscle activation during computerized dynamic posturography (CDP) tasks and ankle kinesthesia in individuals with chronic ankle instability (CAI). Methods: Thirty-five men with CAI participated in this study. The experimental procedure followed a repeated measures design. Muscle activation of lower extremity and ankle kinesthesia of participants were measured using four taping treatments, namely, KT, athletic tape (AT), sham tape (ST), and no tape (NT) in a randomized order. Muscle activation was assessed using surface electromyography (sEMG) synchronized with CDP tests from seven lower extremity muscles of the unstable limb. Ankle kinesthesia was measured by using a threshold to detect the passive motion direction of the unstable ankle. Parameters were analyzed by using a one-way repeated measures ANOVA and followed by pairwise comparisons with a Bonferroni correction. Results: No significant difference was observed among different taping treatments for the majority of parameters during CDP. Except for condition 4 with open eyes, sway-referenced surface, and fixed surround in the sensory organization test (SOT), gastrocnemius medialis root mean square (RMS) was 28.19% lower in AT compared with NT (p = 0.021, 95% CI = 0.002–0.039), while gastrocnemius lateralis RMS was 20.25% lower in AT compared with KT (p = 0.038, 95% CI = 0.000–0.021). In forward-small sudden translation from motor control test (MCT), for peroneal longus (PL), RMS was 24.04% lower in KT compared with ST (p = 0.036, 95% CI = 0.000–0.018). In toes-down sudden rotation from adaption test (ADT), for PL, RMS was 23.41% lower in AT compared with ST (p = 0.015, 95% CI = 0.002–0.027). In addition, no significant difference was observed for a threshold to the detection of passive motion direction among different taping treatments. Conclusion: This study indicated that KT had minimal effect on the muscle activation of the unstable lower limb during static stance, self-initiated, and externally triggered perturbation tasks from CDP and ankle kinesthesia among individuals with CAI, suggesting that the benefit of KT was too small to be clinically worthwhile during application for CAI.